FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILANIMPLEMENTASI STANDAR AKUNTANSI PEMERINTAHANBERBASIS AKRUAL : SEBUAH STUDI EMPIRIS PADA PEMERINTAHAN KOTA BOGOR - Marsdenia, Marsdenia; H, Mutiha Arthaingan (UI Scholars Hub, 2016)
This research has objective to examine if factors Commitment to Organization, Human Resourses, Communication and Infrastructure influence the success of implemention of accrual basis in preparing local Government financial statement. This is a quantitative approach research which is used questionnaires to respondent research by using linier regression equation for analysis. The result is, only factors commitment and communication influenced the success of implementation process of accrual basis and factors human resources and infrastructure did not influenced the success of implementation.